Effect of Natural Antioxidant Extracted From Rosemary Leaves On Stability Of Soybean Oil Under Thermoxidation (Damascus University Journal of agriculture sciences, 2021)
This research was carried out in the directorate of laboratories- ministry of Internal Trade and consumer protection and also the Department of Food Science - Faculty of Agriculture, Damascus University to determine antioxidant activity of ethanolic and oily extracts  of  Rosemary ( Rosmarinus officinalis). The  extracts were added  to soybean oil stored for 5 weeks in the oven at 65 °C and compared with  the  synthetic  antioxidant  (BHA). The antioxidant efficacy of ethanolic  rosemary extracts  with different concentrations (1000  and 2000 ppm) and oily extract 2%  was estimated in  accelerated oxidation  conditions  (Schaal oven test) by estimating peroxide value,  free fatty acid% (Oleic acid) and total polar compounds. The results showed that Rosmary ethanolic extract  with  2000 ppm  had the highest antioxidant effect, while  oily extract 2% had  little effect on the protection of soybean oil from degradation during storage
Keywords: Rosmary